The effects of crude oil price volatility, stock price, exchange rate and interest rate on Malaysia’s economic growth - Rahim, Farah; Hamid, Zarinah (Springer, 2020)
This study examines the effects and relationships between Malaysia’s economic growth and selected variables which are oil price volatility, stock price, real exchange rate and real interest rate. Using time-series data methodology, the study employs unit root test using Augmented Dickey–Fuller (ADF) and Phillips–Perron (PP), Auto-Regressive Distribution Lag (ARDL) model supplemented by Bounds F-Testing, Johansen-Julius Co-integration test and Granger causality test. The longrun equation derived from ARDL shows that there are positive relationships for stock price and real exchange rate whilst there are negative relationships between oil price volatility and real interest rate. Furthermore, Granger causality test shows that only stock price and real interest rates have an impact on Malaysia’s gross domestic product (GDP) in the short run. Finally, sound policy recommendations are suggested, in particular, to address oil price volatility in a forward looking manner as well as monetary-friendly measures to further support Malaysia’s economic growth.